REKONSTRUKSI MANAJEMEN PESANTREN - Noviyanti, Shobihatul Fitroh; Abdul Haris; Marno; Moh Romzi (Pascasarjana Universitas Al-Qolam Malang, 2025)
The reconstruction of pesantren management is a strategic step to integrate traditional values with modernization in response to the challenges of globalization and contemporary developments. This article discusses the importance of such integration in creating pesantren that are relevant, adaptive, and competitive. By promoting transformational leadership and performance-based management, pesantren can enhance operational effectiveness and educational quality. Case studies of Pesantren Daar el-Qolam and Pesantren Al-Azhar demonstrate that implementing an integrative curriculum, utilizing technology in learning, and establishing community-based economic empowerment programs can strengthen the role of pesantren as centers of education and community development. The findings affirm that pesantren, while preserving Islamic values and traditions, can transform into educational institutions capable of producing competent, well-characterized graduates who are ready to contribute to socio-economic development. Therefore, pesantren management reconstruction must be continuously carried out to ensure its relevance and effectiveness in navigating the dynamics of the modern world.